Impact of NAFLD on clinical outcomes in hepatocellular carcinoma treated with sorafenib: an international cohort study. (September 2022) - Howell, Jessica; Samani, Amit; Mannan, Binish; Hajiev, Saur; Motedayen Aval, Leila; Abdelmalak, Rebecca; Tam, Vincent C.; Bettinger, Dominik; Thimme, Robert; Taddei, Tamar H.; Kaplan, David E.; Seidensticker, Max; et al.
Background: The impact of nonalcoholic fatty liver disease (NAFLD) on overall survival (OS), treatment response and toxicity in patients with hepatocellular carcinoma (HCC) treated with sorafenib is unknown. We examined the impact of NAFLD on survival and toxicity in an international cohort of patients receiving sorafenib. Methods: Clinical and demographic data were collected from patients consecutively treated at specialist centres in Europe and North America. The impact of NAFLD on OS, sorafenib-specific survival and toxicity compared with other aetiologies of liver disease using multivariable Cox-proportional hazards and logistic regression modelling was assessed. Results: A total of 5201 patients received sorafenib; 183 (3.6%) had NAFLD-associated HCC. NAFLD-associated HCC patients were more likely to be older women (median age 65.8 versus 63.0 years, p  < 0.01 and 10.4% versus 2.3%,  < 0.01), with a median body mass index (BMI) of 29.4. After controlling for known prognostic factors, no difference in OS in patients with or without NAFLD was observed [hazard ratio (HR): 0.99, 95% confidence interval (CI): 0.84–1.18, p  = 0.98]. NAFLD-associated patients had more advanced stage HCC when they commenced sorafenib [Barcelona Clinic Liver Class (BCLC) C/D 70.9% versus 58.9%, p  < 0.01] and were more likely to be commenced on a lower starting dose of sorafenib (51.4 versus 36.4%, p  < 0.01). There was no difference in sorafenib-specific survival between NAFLD and other aetiologies (HR: 0.96, 95% CI: 0.79–1.17, p  = 0.96). Adverse events were similar between NAFLD and non-NAFLD HCC groups, including rates of greater than grade 2 hypertension (6.3% versus 5.8%, p  = 1.00). Conclusion: Survival in HCC does not appear to be influenced by the presence of NAFLD. NAFLD-associated HCC derive similar clinical benefit from sorafenib compared with other aetiologies.